Myostatin inhibition in combination with antisense oligonucleotide therapy improves outcomes in spinal muscular atrophy. Issue 3 (7th February 2020) - Zhou, Haiyan; Meng, Jinhong; Malerba, Alberto; Catapano, Francesco; Sintusek, Palittiya; Jarmin, Susan; Feng, Lucy; Lu‐Nguyen, Ngoc; Sun, Lianwen; Mariot, Virginie; Dumonceaux, Julie; Morgan, Jennifer E.; et al.
Abstract: Background: Spinal muscular atrophy (SMA) is caused by genetic defects in the survival motor neuron 1 ( SMN1 ) gene that lead to SMN deficiency. Different SMN‐restoring therapies substantially prolong survival and function in transgenic mice of SMA. However, these therapies do not entirely prevent muscle atrophy and restore function completely. To further improve the outcome, we explored the potential of a combinatorial therapy by modulating SMN production and muscle‐enhancing approach as a novel therapeutic strategy for SMA. Methods: The experiments were performed in a mouse model of severe SMA. A previously reported 25‐mer morpholino antisense oligomer PMO25 was used to restore SMN expression. The adeno‐associated virus‐mediated expression of myostatin propeptide was used to block the myostatin pathway. Newborn SMA mice were treated with a single subcutaneous injection of 40 μg/g (therapeutic dose) or 10 μg/g (low‐dose) PMO25 on its own or together with systemic delivery of a single dose of adeno‐associated virus‐mediated expression of myostatin propeptide. The multiple effects of myostatin inhibition on survival, skeletal muscle phenotype, motor function, neuromuscular junction maturation, and proprioceptive afferences were evaluated. Results: We show that myostatin inhibition acts synergistically with SMN‐restoring antisense therapy in SMA mice treated with the higher therapeutic dose PMO25 (40 μg/g), by increasing not only body weight (21% increase in male mice at Day 40), muscle mass (38% increase), and fibre size (35% increase in tibialis anterior muscle in 3 month female SMA mice), but also motor function and physical performance as measured in hanging wire test (two‐fold increase in time score) and treadmill exercise test (two‐fold increase in running distance). In SMA mice treated with low‐dose PMO25 (10 μg/g), the early application of myostatin inhibition prolongs survival (40% increase), improves neuromuscular junction maturation (50% increase) and innervation (30% increase), and increases both the size of sensory neurons in dorsal root ganglia (60% increase) and the preservation of proprioceptive synapses in the spinal cord (30% increase). Conclusions: These data suggest that myostatin inhibition, in addition to the well‐known effect on muscle mass, can also positively influence the sensory neural circuits that may enhance motor neurons function. While the availability of the antisense drug Spinraza for SMA and other SMN‐enhancing therapies has provided unprecedented improvement in SMA patients, there are still unmet needs in these patients. Our study provides further rationale for considering myostatin inhibitors as a therapeutic intervention in SMA patients, in combination with SMN‐restoring drugs.